Jejak Historis Raden Mas Said sebagai Sumber Identitas Politik Kabupaten Wonogiri - Retno Widianto; Hieronymus Purwanta; Sudiyanto Sudiyanto (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Wonogiri is a regency that is part of the struggle of Raden Mas Said in establishing the Praja Mangkunegaran, leaving a historical trace in the Wonogiri region. The historical traces, which include physical remnants such as locations of significance, tombs, and springs, serve as evidence of Raden Mas Said's existence. The motto and spirit of Raden Mas Said's struggle still resonate within the community. This research aims to uncover the historical traces of Raden Mas Said in the Wonogiri regency and to understand the role of these relics in shaping political identity within the region. This study employs a qualitative approach using historical research methods, which consist of heuristic, criticism, interpretation, and historiography stages, with a focus on collective identity. The findings indicate the significant role of Raden Mas Said's activities in relation to the existence of the regency and the community of Wonogiri. In conclusion, Wonogiri has a collective identity as a society that has spiritual principles and great solidarity formed by the sense of sacrifice that has been made by Raden Mas Said.